The Hagfeldt Donor and Use of Next‐Generation Bulky Donor Designs in Dye‐Sensitized Solar Cells. Issue 10 (25th March 2020) - Baumann, Alexandra; Curiac, Christine; Delcamp, Jared H.
Abstract: "The Hagfeldt donor" is a bulky triarylamine building block with four alkyl chains in a 3‐dimensional arrangement that is used with organic dyes in dye‐sensitized solar cells (DSCs) in over 140 publications. Many of the highest performing DSC devices in literature make use of this group due to exceptional TiO2 surface protection properties, which slows recombination of electrons in TiO2 with the electrolyte. Importantly, record‐setting cobalt and copper redox shuttle‐based DSCs require exceptional surface protection to slow a facile recombination of electrons to these positively charged redox shuttles. Several syntheses have emerged for the Hagfeldt donor due to the need for iterative aryl–halide cross‐ coupling reactions complicating a straightforward route. Six synthetic strategies found in literature are described along with the challenges of each route. A recent method that has been put forward in the literature as a scalable, regioisomerically pure route is highlighted. Abstract : Six routes, the good and the bad : This Minireview focuses on the synthesis of a molecular motif, the Hagfeldt donor, that has found widespread use in dye‐sensitized applications. This building block motif is both incredibly prevalent and has a diverse array of synthetic routes accessing it. Six distinct synthetic routes to this material have been identified in the literature, and each approach is discussed in terms of synthetic efficiency and apparent pitfalls.